INTERNATIONAL ASSESSMENT PROGRAMS USED IN PRIMARY SCHOOL MATHEMATICS AS A FACTOR IN DEVELOPING LOGICAL THINKING - Ermamatova Maftuna Ermamtovna; Saydullayeva Dilrusor (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: This thesis explores the implementation of international assessment programs (TIMSS, PIRLS, and PISA) in primary school mathematics lessons and their role in developing students’ logical thinking. These programs not only assess students’ knowledge but also evaluate their analytical abilities and practical application of knowledge.